Feeding flaxseed to chicken hens changes the size and fatty acid composition of their chicks’ brains - Whittle, Rosemary H.; Kiarie, Elijah G.; Ma, David W. L.; Widowski, Tina M. (Frontiers in Physiology, 2024)
Diets fed to commercial chicken breeders are high in n-6 fatty acids (n-6 FAs) and low in n-3 fatty acids (n-3 FAs). N-3 FAs are essential for embryonic brain development. In precocial birds, like chickens, brain development and brain n-3 FA accrual occur primarily before hatching. In two experiments, broiler and layer breeders were fed diets with or without flaxseed as the source of n-3 FAs from plant-based alpha-linolenic acid. Day-old broiler (n = 80) and layer (n = 96) offspring were dissected to calculate the percentage brain-to-body weight. Brain FA analyses from total lipid extracts were determined in the broiler (n = 24) and layer (n = 24) offspring brains, and the percentage FA composition and concentration (µg FAs per g brain) were calculated for each n-3 and n-6 FA. The brain size was only increased in broiler offspring from mothers fed flaxseed (χ2 = 9.22, p = 0.002). In layer offspring only, the maternal flaxseed diet increased the brain concentration and percentage of n-3 FAs and decreased n-6 FAs (p < 0.05). We showed that feeding flaxseed to mothers increased the brain size in broiler offspring and altered brain FA composition in layer offspring. These results may have implications for poultry and other captive bird species fed diets low in n-3 FAs.